Strengthening China's national biodiversity strategy to attain an ecological civilization. Issue 5 (10th June 2019) - Wu, Ruidong; Possingham, Hugh P.; Yu, Guangzhi; Jin, Tong; Wang, Junjun; Yang, Feiling; Liu, Shiliang; Ma, Jianzhong; Liu, Xi; Zhao, Haiwei
Abstract: Biodiversity conservation is essential for realizing China's new vision of an ecological civilization. China has been implementing numerous massive ecological sustainability and protected area (ES&PA) programs across the entire country. These programs have greatly restored degraded ecological environments, improved provisions of critical ecosystem services and increased rural livelihoods. However, despite the general improvements in environmental quality, the trend of rapid biodiversity loss has not been significantly reduced. We found that most of the current ES&PA programs lack explicit biodiversity goals, and thus have limited contributions to the conservation of biodiversity. Given the limited resources available for and huge investments associated with these programs, achieving greater biodiversity gains under them is the most cost‐effective way to conserve biodiversity. We recommend six strategies for strengthening the country's biodiversity conservation, that is, strengthening biodiversity in ES&PA programs, PAs as the core, integrating biodiversity and ecosystem services, delivering effective monitoring, broad inclusiveness of stakeholders and mainstreaming biodiversity. These strategies also highlight China's priorities for achieving significant progresses toward the Strategic Plan for Biodiversity 2011–2020, and should be important options for developing China's post‐2020 biodiversity framework.